The Latin American perspective in the History textbooks (Quinto Sol, 2013)
This paper analyzes the views that mostly prevail in History textbooks concerning Latin America in the period between 1980 and 2000, with the purpose of recognizing continuities and breaches in the formulation of historical curricula contents. Such perspective seeks to study pre-eminent discourses about these issues related with the conformation of Latin American nationalities and the ideas that these stories imply concerning the citizens´ education.
Keywords: Teaching of History; school textbooks; Latin American History; citizenship